Two mechanisms of ball impact that determine the horizontal direction of batted ball velocity in baseball: Their contributions to batted ball speed - Kidokoro, S.; Yanai, T. (Japan Journal of Physical Education, Health and Sport Sciences, 2017)
The horizontal direction in which a batted ball travels is determined primarily by two factors: the horizontal angle of the bat at ball impact (first mechanism) and the interaction between the vertical inclination angle of the bat and the position of the ball impact along the short axis of the bat (second mechanism). As the bat is generally inclined vertically at the moment of ball impact (the head is positioned lower than the grip end), the second mechanism must cause an opposite influence on the horizontal trajectory of the batted ball when a grounder and a fly-ball are compared. The purposes of this study were two-fold: (a) to compare the contributions of the two mechanisms to the horizontal direction of batted balls between grounders and fly-balls and (b) to determine the relationship between the contribution of each mechanism and the speed of the batted ball. Sixteen collegiate baseball players were asked to hit balls delivered by a pitching machine aiming towards the same field and the opposite field for four trials each. The motions of the ball and the bat around the moment of ball impact were recorded using two high-speed cameras (1000 fps). The contributions of the two mechanisms to the horizontal directions of the batted balls were calculated from the following variables: the trajectory of the pitched and batted ball, projection angles of the bat in the horizontal plane (horizontal bat angle) and the vertical plane (vertical bat angle), and the angle of the line of impact from the horizontal at ball impact (line of impact angle). The first mechanism contributed 40% or more on average to both the same- and opposite-field hitting of grounders and fly-balls projected towards the fair territory. For fly-balls to the same field and grounders to the opposite field, the contribution of the first mechanism was particularly high (same/fly ball: 118.6±35.2%, opposite/grounder: 109.5±17.8%), and the impact surface of the bat faced toward the batted ball direction. The contribution of the second mechanism was greater for grounders to the same field and fly-balls to the opposite field than the others (same/grounder: 46.7±23.3%, opposite/fly ball: 50.6±49.2%). The speed of the batted ball was negatively correlated with the contribution of the second mechanism (r=-0.73, p<0.01). Therefore, in order to hit a ball with higher speed, a batter should adjust the timing of impact to use the first mechanism, and should strike near the center of the ball.